Status and molecular identification of arbuscular mycorrhizal (AM) fungi associated with Acacia spp. on rehabilitated gold and uranium mine tailings - Buck, Michelle Toni (My University, 2015)
Phytoremeditation of mine tailings provides the most cost-effective means of alleviating their pollutant effects. Research has shown that successful revegetation of mine tailings can be optimised by providing appropriate microbial symbionts for the plants. The aim of this study was to assess the arbuscular mycorrhizal (AM) status of trees currently being used for phytoremediation trials of mine tailings in the Welkom gold fields, and to determine the AM fungal diversity of these sites. The Acacia spp. analysed were growing on rehabilitated gold and uranium mine tailings which had undergone different rehabilitation regimes. Planted acacia trees which had been inoculated with crude AM fungal inocula were present on one mine tailing site as compared to the second mine tailing site on which the acacias were naturally colonisers and the site had been ameliorated with garden refuse. Root and slime samples were collected in early spring and half if each initial sample was used immediately for colonisation analysis and to identify AM fungi through molecular analysis of the small subunit rRNS gene sequences; the other half of each sample was used to produce trap cultures which were used later for colonisation and molecular analysis. Total AM fungal colonisation of initial samples for planted acacies was 19 % and for naturally colonising acacias was 66 %. The total AM fungal colonisation of trap culture samples for planted acacias increased to 32 % and for naturallhy colonising acacias it increased to 78 %. Spore counts of initial samples averaged 402 spores per 100 g-1 soil for planted acacias and 455 spores per 100 g-1 soil for naturally colonising acacias. For trap culture samples, spore counts decreased by approximately 50 %. The AM fungi identified fell within 8 genera, namely, Diversispora, Rhizophagus, Scutellospora, Claroideoglomus, Cetraspora, Sclerocystis, Glomus and Redecker. The study represents a first report utilising molecular biosystematics with AM fungal DNA from colonised roots as the template. The results will assist in making decisions about future AM fungal surveys and applying AM fungal inoculum in phytoremediation trials of mine waste sites. Key words: Phytoremediation, mine tailings, arbuscular mycorrhizal (AM) fungus, Acacia, molecular identification, SSU rRNA gene sequence
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science.
Keywords: Vesicular-arbuscular mycorrhizas.; Gold mines and mining.; Uranium mine and mining.